Epigenetic Quantification of DNA 5‐Hydroxymethylcytosine Using DNA Hybridization‐Based Single‐Molecule Immunofluorescent Imaging. Issue 5 (15th April 2021) - Du, Yang; Lai, Ying; Liu, Ji‐Yan; Diao, Jiajie
Abstract: 5‐Hydroxymethylcytosine (5hmC) is a deoxyribonucleic acid (DNA) epigenetic modification that has an important function in embryonic development and human diseases. However, the numerous methods that have been developed to detect and quantify 5hmC, require large amounts of DNA sample to be modified via chemical reactions, which considerably limits their application with cell‐free DNA (cfDNA). Meanwhile, other antibody‐based methods of detecting 5hmC do not offer information about the DNA sequence. Here, in this article DNA hybridization‐based single‐molecule immunofluorescent imaging is presented, an ultrasensitive method of detecting 5hmC modification in DNA. Via using the probe DNA to capture the DNA fragment of interest and the 5hmC antibody to detect the 5hmC modification in DNA, the fluorescent response signal of the 5hmC modification from the secondary antibody at the single‐molecule level is successfully detected. Using the method, one could determine the quantity of 5hmC in the gene of interest within 6 h. In addition, it requires only 3 pg of the DNA sample and minimal experience and training for operation and analysis. Abstract : An ultrasensitive 5‐hydroxymethylcytosine quantification method that is potentially valuable for studying epigenetic in cell‐free DNA of interest as a liquid biopsy technique, consists of three key components: DNA probe in charge of capturing DNA fragments of interest, antibody responsible for converting biosignals of 5‐hydroxymethylcytosine to fluorescence signals, and total internal reflection fluorescence microscopy for identifying and quantifying these fluorescence signals.